Interpersonal Communication Of Teacher - Deaf Students In Online Learning - Lusiyana, Annisa; Ramadhana, Maulana Rezi (Syntax Literate, 2023)
In creating satisfying interactions, it requires interpersonal communication that goes both ways between teachers and deaf students in online learning. This study aims to find out how interpersonal communication occurs between deaf teachers and students in online learning which is studied using symbolic interaction theory in S Public Special Education School Bekasi Regency. This research used a qualitative research method by collecting data through interviews with twelve informants who were divided into key informants and supporting informants, namely six teachers and six deaf students of Public Special Education School Bekasi Regency with data analysis using ATLAS.ti software. The results show that there are three aspects of symbolic interaction in interpersonal communication carried out by deaf teachers and students in online learning, including 1) Mind, resulting in the theme of online learning situations, 2) Self, producing the theme of interaction with children, 3) Society, resulting in the theme of building interaction. These three aspects give rise to four categories, including technical barriers, non-technical barriers, interaction approach strategies, and providing support to children. This research can help provide information about interpersonal communication carried out by deaf teachers and students in online learning.